2020
DOI: 10.2174/1874285802014010072
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activities of Culture-dependent Bacteria Isolated from Apis nigrocincta Gut

Abstract: Introduction: Apis nigrocincta is a honeybee endemic to Mindanao island (the Philippines), Sangihe island (North Sulawesi, Indonesia) and Sulawesi mainland (Indonesia). The genus Apis is well known to have symbiont in their guts, which helps balance the microbiome in the gut and host health. Objective: The objective of this study was to determine whether the bacteria isolated from the gut of honeybee Apis nigrocincta produce metabolites with potential growth inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
(9 reference statements)
1
6
0
Order By: Relevance
“…Three isolates showing strong and very strong activities against N. gonorrhoeae were identified molecularly as B. cereus, while one isolate was identified as A. indicus, which shared 100% identity with the reference bacteria in GenBank. Similar results for the activity of B. cereus were reported by Lombogia et al [51], who found that B. cereus from the gut of A. nigrocincta had antibacterial effects against S. aureus and Escherichia coli. In their heat-inactivated form, various strains of bacteria, such as lactic acid bacteria and bifidobacteria, can produce beneficial effects [52].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Three isolates showing strong and very strong activities against N. gonorrhoeae were identified molecularly as B. cereus, while one isolate was identified as A. indicus, which shared 100% identity with the reference bacteria in GenBank. Similar results for the activity of B. cereus were reported by Lombogia et al [51], who found that B. cereus from the gut of A. nigrocincta had antibacterial effects against S. aureus and Escherichia coli. In their heat-inactivated form, various strains of bacteria, such as lactic acid bacteria and bifidobacteria, can produce beneficial effects [52].…”
Section: Discussionsupporting
confidence: 89%
“…The following procedure was based on Lombogia et al [51]. The gut of A. dorsata was aseptically removed and then placed in Eppendorf tubes containing sterile physiological solution (NaCl 0.95%) and homogenized using a sterile micropestle.…”
Section: Isolation and Purification Of Bacteria From Honeybee Gutmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Lombogia et al ( 92 ), the presence of bacteria in the digestive system that produces dominant metabolites helps maintain a balanced environment. Bioactive molecules with potent antibacterial activity against various pathogenic bacteria, including enterotoxigenic E. coli, Salmonella , and Staphylococcus aureus , were discovered in organisms found in panda feces and fish ( 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of selected isolates was determined by the conventional method refers to Bergey's Manual of Systematic Bacteriology [9]. The identification includes microbiological tests, biochemical tests, and catalase production test.…”
Section: Identification Of Superior Isolatesmentioning
confidence: 99%